Intravascular immune hemolysis caused by the contrast medium iomeprol. Issue 10 (24th January 2013) - Mayer, Beate; Leo, Albrecht; Herziger, Angela; Houben, Philipp; Schemmer, Peter; Salama, Abdulgabar
<x xml:space="preserve">Abstract</x> Background Immune‐mediated hemolysis is not included in the list of adverse reactions related to contrast medium (CM). Here, we report on a patient who developed immune hemolytic anemia (IHA) related to iomeprol, a nonionic CM. Study Design and Methods A 34‐year‐old female patient developed massive hemolysis during infusion of 50 mL of iomeprol. Serologic studies were performed using standard techniques. Results Before hemolysis, the patient's serum was weakly positive with e+ red blood cells (RBCs; autoanti‐e) and the direct antiglobulin test (DAT) was negative. After hemolysis, the patient's serum samples became significantly reactive with e– RBCs in the presence of iomeprol but not in the presence of two other similar CM. The DAT became strongly positive only with anti‐C3d. Conclusion Initially, an allergic reaction was suggested, and as the hemolysis became obvious, a toxic hemolysis was suspected. However, serologic reexamination revealed an iomeprol‐dependent antibody. IHA related to CM has yet only been described in one patient in 1991. The hemolysis in that patient was related to Isopaque, an older ionic CM. Here, we describe an additional patient and recommend that CM should be considered as a rare risk in the development of IHA.